Randomised non‐inferiority trial: 1600 mg versus 400 mg tablets of mesalazine for the treatment of mild‐to‐moderate ulcerative colitis. Issue 3 (1st June 2017) - D'Haens, G. R.; Sandborn, W. J.; Zou, G.; Stitt, L. W.; Rutgeerts, P. J.; Gilgen, D.; Jairath, V.; Hindryckx, P.; Shackelton, L. M.; Vandervoort, M. K.; Parker, C. E.; Muller, C.; et al.
Summary: Background: High concentration mesalazine formulations are more convenient than conventional low concentration formulations for the treatment of ulcerative colitis (UC). Aim: To compare the efficacy and safety of 1600 mg and 400 mg tablet mesalazine formulations. Methods: Patients with mild‐to‐moderate active UC (Mayo Clinic Score >5; N=817) were randomised to 3.2 g of oral mesalazine, administered as two 1600 mg tablets once, or four 400 mg tablets twice daily. We hypothesised that treatment with the 1600 mg tablet was non‐inferior (within a 10% margin) to the 400 mg tablet for induction of clinical and endoscopic remission at week 8. Open‐label treatment with the 1600 mg tablet continued for 26‐30 weeks based on induction response. Predictors of treatment response were also explored. Results: At week 8, remission occurred in 22.4% and 24.6% of patients receiving the 1600 mg and 400 mg tablets, respectively (absolute difference −2.2%, 95% CI: −8.1% to 3.8%, non‐inferiority P =.005). Endoscopic and histopathologic disease activity, leucocyte concentration and age were significantly associated with clinical remission ( P =.022, .042, .014 and .023, respectively). At week 38, 43.9% (296/675) of patients who continued treatment with the 1600 mg formulation were in remission, including 70.3% (142/202) of patients who received a reduced dose of mesalazine (1.6 g/d). The overall incidence of serious adverse events was low. Conclusions: Induction therapy with 3.2 mg mesalazine using two 1600 mg tablets once‐daily was statistically and clinically non‐inferior to a twice‐daily regimen using four 400 mg tablets (NCT01903252).